Customer Loyalty and commitment towards Organizational Growth and Customer Satisfaction - Awan, Asif Iqbal; Raja, Yasir Mehmood; Ahmed, Mushtaq; Zaman, Hafiz Muhammad Fakhar (IJRDO - Journal of Applied Management Science, 2015)
Factors affecting customer loyalty have immense weightage in order to identify the reasons or the factors which are accountable to create loyalty among customers for a fastidious brand. Purpose The purpose of the study is to classify the role of customer loyalty in terms of sustaining continuous organizational growth in highly competitive Pakistani market and factor affecting customer loyalty and their impact on organization growth. The most recent and relevant studies contained by the literature have been included and summated in this paper. All results are based on the overview of previous studies. Findings The review of previous studies and some research work about the factor affecting customer loyalty and their impact on organization growth and development. In these researches different service providers were embattled as the population whereas customer services and Price Fairness were taken as predicting variables towards criterion variable which is customer’s loyalty. The outcomes conclude that both the factors considerably contributed to explain customer’s satisfaction and loyalty but relatively price fairness had the bigger impact on customer loyalty than customer’s services and organizational growth. Results and implications of the study are also discussed based on the analysis and findings.